2021
DOI: 10.1093/eurpub/ckab179
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of working hours in later careers and their association with social and health-related factors: a follow-up study

Abstract: Background The aim was to identify working hours’ trajectories in later work careers over a follow-up of 15–17 years and to examine their association with social factors and health. Methods A subsample from the Helsinki Health Study was extracted comprising employees of the City of Helsinki, Finland. Growth mixture modelling was used to identify different working hour trajectories. Age, gender, occupational class, marital sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Leisure time physical activity was estimated using the metabolic equivalent (MET) index [ 30 ] and divided into three groups: low (< 14 MET-hours/week), intermediate (≥ 14 MET-hours/week with only moderate activity) and high (≥ 14 MET-hours/week including vigorous activity). For each participant, the covariates were derived from the questionnaires using the mode [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Leisure time physical activity was estimated using the metabolic equivalent (MET) index [ 30 ] and divided into three groups: low (< 14 MET-hours/week), intermediate (≥ 14 MET-hours/week with only moderate activity) and high (≥ 14 MET-hours/week including vigorous activity). For each participant, the covariates were derived from the questionnaires using the mode [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The likelihood of this trajectory was higher in women and in higher socioeconomic status ( 20 ). One previous study identified trajectories of working hours and found that female sex, age, lifestyle risk factors, and health problems were associated with short and varying working hours ( 21 ). The study did not account for simultaneous changes in self-rated health, and used subjective evaluations on working hours.…”
Section: Introductionmentioning
confidence: 99%